A new species of slender coralsnake from Colombia, and its clinal an ontogenetic variation (Serpentes, Elapidae: Leptomicrurus) - Lamar, William W. (Revista de Biología Tropical, 2003)
Leptomicrurus renjifoi is described from tropical semi-deciduous forest of the eastern Colombian llanos. It is one of the smallest species in the genus, is most similar to L. scutiventris, and it may be distinguished from known congeners by a combination of color, pattern, and scale characters. Evidence for the recognition of Leptomicrurus is convincing, although its members were recently thought to comprise a closely related assemblage within Micrurus. A supposedly aberrant specimen of L. scutiventris may indicate clinal or ontogenetic variation in pattern.